EFFICACY AND SAFE USE OF SPECIFIC ANGIOTENSIN II RECEPTOR ANTAGONIST IRBESARTAN FOR CURING ARTERIAL HYPERTENSION IN CHILDREN AND TEENAGERS: A CLINICAL STUDY - L.P. Zharkova; I.V. Andreeva ("Paediatrician" Publishers LLC, 2007)
A prolonged open non comparative study of efficacy and safety of various doses of specific angiotensin II (type at1) irbesartan for curing arterial hypertension in children and teenagers was carried out. The average irbesartan efficacy in Ag monotherapy in children was 92,5%, in the younger group efficacy was somewhat higher than in the teenagers (95,7% compared to 88,2%, p < 0,05). On average, prolonged arterial hypertension therapy with various doses of irbesartan (from 0,5 to 0,5 mg/kg per day) in children reduces systolitic arterial pressure by 25,8 mm m.c. (17,9%) compared to the initial value, and diastolitic arterial pressure decreases by 13,8 mm m.c. (17,7%). Irbesartan therapy revealed good acceptability of the medicine.Key words: children's arterial hypertension, specific receptor antagonist ii irbesartan, efficacy, safety, acceptability, children.